BIODIESEL PRODUCTION FROM WASTE FISH CANNING OIL USING COCOPEAT ASH CATALYST - Siti Diah Ayu Febriani; Prisca Amalia Nofitasari; Saiful Anwar (Universitas Mercu Buana, 2023)
Biodiesel is an environmentally friendly alternative fuel for diesel engines. The research studies the extraction process of biodiesel from waste produced by a fish canning factory using a heterogeneous catalyst known as cocopeat ash. The experiment was designed utilizing a completely randomized design with two factorial treatments and four repetitions. The primary factor under investigation was the composition of the catalyst, specifically 3%, 5%, and 7% w/v methanol. The second factor examined was the reaction time of either 60 minutes or 120 minutes. Data analysis revealed variations in density, viscosity, acid number, and Free Fatty Acids (FFA) in fish oil before and after refinement. The treatment that yielded the highest results was A3B2, featuring a catalyst composition of 7% and a reaction time duration of two hours, which achieved an impressive biodiesel yield of 81%. Moreover, several parameters tested for compliance with SNI-04-7182-2015 standards showed positive outcomes. These parameters include a density value measuring 876.3 kg/m³, the flash point around 160°C, iodine number reaching 16.36 g/100g, and heating value 47.47 MJ/Kg.